(untitled) (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2023)
This study aims to determine the incidence of Brucellosis in Bali cattle in Bolo district, Bima regency, based on serological tests (seroprevalence). The sample used in this study was cattle serum. Serum samples were obtained from 70 Bali cattle aged over one year. The detection method, namely the Rose Bengal Test, detects the incidence of Brucellosis. Samples in the form of serum are reacted with Brucella sp. antigen to see antibodies in the serum. The working principle of the Rose Bengal Test is to see whether there is agglutination or not. The results of this study will be an indicator to determine the presence or absence of Brucellosis in Bali cattle in Bolo district, Bima regency. Then the monitoring and control can be established by relevant stakeholders, especially the Livestock and Animal Health Service of Bima Regency. The data obtained from serum samples that describe the positive or negative for Brucellosis is presented descriptively by explaining each sample origin’s seropositive and seronegative results. The results showed that in all samples from Bali cattle in the District of Bolo, as many as 70 samples reacted negatively to the Rose Bengal Test. This result indicates that the cattle on Sumbawa Island are not infected with Brucellosis. Keywords: Brucellosis, Reproductive Disorders, Bali Cattle, Rose Bengal Test